Justification of Taxation with Flat-Rate Income Tax on Real Estate Renting for Tourist Purposes in the Republic of Croatia - Luka Pribisalić (LeXonomica, 2022)
Income from renting apartments, rooms, and beds to travelers and tourists and organizing camps in the Republic of Croatia is taxed at a flat rate. The question is whether the taxation of this type of activity is justified if it generates more income than from renting/leasing real estate under a lease or rental agreement when these activities are taxed with a higher amount of tax from renting real estate for tourism purposes. Therefore, it is necessary to analyze why the flat-rate taxation regime for the activity of renting apartments, rooms, and beds to travelers and tourists and the organization of camps is prescribed in the Republic of Croatia and whether it is justified.Povzetek. Prihodki od oddajanja stanovanj, sob in ležišč potnikom in turistom ter organiziranja kampov v Republiki Hrvaški so obdavčeni po pavšalni stopnji. Vprašanje je, ali je obdavčitev te vrste dejavnosti upravičena, če se z njo ustvari večji dohodek kot z najemom/izposojo nepremičnin na podlagi zakupne ali najemne pogodbe, ko so te dejavnosti obdavčene z višjim zneskom davka od oddajanja nepremičnin v turistične namene. Zato je treba analizirati, zakaj je v Republiki Hrvaški predpisan pavšalni režim obdavčitve za dejavnost oddajanja apartmajev, sob in ležišč potnikom in turistom ter organizacijo kampov in ali je upravičen.